SOCIAL CONSTRUCTION OF MUSLIM YOUTH TOWARDS CHINESE CULTURE THROUGH THE KIMSIN MAKCO PARADE, SEMBAHYANG REBUTAN, AND BARONGSAI IN SODITAN VILLAGE, LASEM DISTRICT, REMBANG REGENCY: Konstruksi Sosial Remaja Muslim terhadap Budaya Tionghoa Melalui Kirab Kimsin Makco, Sembahyang Rebutan, Barongsai di Desa Soditan, Kecamatan Lasem Kabupaten Rembang - hasib widya Azzahid; Wasino Wasino (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to understand the dynamics of Muslim adolescents in Soditan Village constructing their views and attitudes toward Chinese cultural practices, particularly the Kirab Kimsin Makco, Sembahyang Rebutan, and Barongsai, through a qualitative phenomenological approach. The analysis was conducted through the stages of data reduction, data presentation, and verification. The results show that adolescents' understanding is not singular, but rather formed from direct experience, family dialogue, advice from religious leaders, and historical narratives of cultural figures. Their interactions with Chinese culture are directed. They participate as spectators, volunteers, or supporters of events, but consistently maintain the boundary between social participation and the realm of religious ritual. Ultimately, the resulting social construction reflects a pattern of active tolerance, where religious identity is maintained without creating social distance from the Chinese community. These findings suggest that harmony in Soditan is not a spontaneous outcome, but rather the product of value negotiations between families, religious institutions, and cultural authorities that are continuously reproduced in the daily lives of adolescents.